Building Wealth Through REITS (Third Edition). - Jayaraman, Bobby. (Marshall Cavendish International (Asia) Private Limited, 2021)
Almost two decades have passed since the launch of Singapore's first REIT (Real Estate Investment Trust) in 2002. Despite that, REITs are not as popular as they deserve to be. Singapore REITs are one of the few businesses that offer a direct play on the domestic economy, and they have proven their resilience through market cycles. Building Wealth Through REITs takes a deep look at this asset class and explains why every investor should take a serious look at REITs. It discusses common perceptions about REITs and why many of them don't hold up to scrutiny. In-depth interviews with the CEOs of 8 major S-REITs (including Parkway Life and Frasers Logistics & Commercial Trust) will stimulate your thinking and further your knowledge of various REITs. This third edition of the book provides a timely analysis of REITs in the age of Covid, with advice on how investors can continue to thrive in trying times. With practical guidance on how to build a strong and high-performing REIT portfolio, you will be on your way to financial freedom much earlier than you thought possible.